Higher education in the era of migration, displacement and internationalization - Arar, Khalid; Kondakci, Yasar; Streitwieser, Bernhard Thomas, 1969-; Saiti, Anna (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book draws from the voices of students and those who educate them to reveal the unique issues faced in in the quest to access higher education in order to provide a greater understanding of the complex phenomenon of international migration and its intersection with higher education. Higher Education in the Era of Migration, Displacement and Internationalization examines how higher education institutions globally can improve to meet the needs of displaced people, refugees, migrants, and international students. Examining relevant policy, leadership, programs, and services that equitably meet diversified students' needs, this book examines how institutions can increase access, participation and success. The chapters present cutting-edge scholarship that tie the existing body of knowledge on international migration for higher education to ways that institutions of higher education can assist the formation of relevant policy towards displaced groups around the globe. Through students' voices from different nations as well as global policy analysis, the book exemplifies how different higher education institutions are widening access pathways for atypical students. This book is essential reading for scholars, policy-makers, and communities of practitioners. It offers a greater understanding of the complex phenomenon of international immigration and its intersection with higher education. By transcending national policy analysis, it extends the subject of refugee and migration studies to a wider audience"--
Definition : atypical international students -- Traversing boundaries, moving between different zones -- Access to higher education for displaced persons : five country cases -- Higher education for displaced persons : lessons from the research -- Displaced students' viewpoints on their higher education experiences -- Support for refugee students at national and international levels -- Higher education for refugees : global discourses and future research.
Keywords: Refugees -- Education (Higher); Immigrants -- Education (Higher); Students, Foreign -- Attitudes; Education, Higher -- Social aspects; Higher education and state; Education, Higher -- Aims and objectives; EDUCATION / General